2014
DOI: 10.1016/j.jaac.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Abnormalities in Youths With Conduct Disorder and Elevated Callous-Unemotional Traits

Abstract: Objective Though there is growing evidence of brain abnormalities among individuals with Conduct Disorder (CD), the structural neuroimaging literature is mixed and frequently aggregates cortical volume rather than differentiating cortical thickness from surface area. The current study assesses CD-related differences in cortical thickness, surface area, and gyrification as well as volume differences in subcortical structures critical to neurodevelopmental models of CD (amygdala; striatum) in a carefully charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 57 publications
11
111
4
1
Order By: Relevance
“…While Wallace et al (2014) did find reduced amygdala volumes in children with CD, no effects were found for CU traits. Similarly, Fairchild et al (2013) note reduced amygdala gray matter volume in adolescents with CD, but no significant differences associated with CU traits.…”
Section: Amygdalamentioning
confidence: 66%
See 2 more Smart Citations
“…While Wallace et al (2014) did find reduced amygdala volumes in children with CD, no effects were found for CU traits. Similarly, Fairchild et al (2013) note reduced amygdala gray matter volume in adolescents with CD, but no significant differences associated with CU traits.…”
Section: Amygdalamentioning
confidence: 66%
“…As shown above, research has demonstrated that psychopaths have structural and functional impairments to the prefrontal cortex, including the ventromedial prefrontal cortex, and the amygdala, both involved in the normal development of punishment association and reward and punishment processing (Baxter & Murray, 2002;Wallace et al, 2014). This potentially provides evidence that psychopaths may be not be deterred from offending or reoffending by severe punishments due to these impairments.…”
Section: Adult Psychopaths In the Criminal Justice Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…Hence, we expected that higher levels of externalizing behavior would be associated with attenuated cortical thinning in dlPFC, OFC, and ACC (Ameis et al., 2014; Oostermeijer et al., 2016). Moreover, we expected a negative relation between externalizing behavior and subcortical development, specifically in striatum, hippocampus, and amygdala volume (Muetzel et al., 2017; Wallace et al., 2014). Finally, we examined the relation between maturational coupling and externalizing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to functional imaging, there have been null indings regarding the structural integrity of the amygdala in children with CU traits [80,81]. Wallace et al found reduced amygdala volumes in children with CD but they noted that CU traits were not efective on this volume.…”
Section: Neurobiological Factorsmentioning
confidence: 99%